Penelitian dan Pengabdian Masyarakat pada Perguruan Tinggi - Idris HM Noor (Jurnal Pendidikan dan Kebudayaan, 2010)
The objectives of the research is to know the implementation of policy and implementation of the research program and the public service at Higher Education (HE). The research method is the mixed of quantitative and qualitative methods with a descriptive analysis. Sample of the research is 160 repondents taken purposively of head and members of the research and public service institutions at public and private of HE. The research was conducted for 7 months from April to October 2008 at six provinces: West Nusa Tenggara province, Bali province, Special Yogyakarta province, West Java province, West Sumatera province, and South Sumatera province. Tools and the techniques of data collecting are using documentation study, questionnaires, inteview, and focus group discussion. Primary data is the information from the resource persons from HE while the secondary data is taken from the documents about the rules as well as the laws and the related research done by other people. The findings of the research are: 1) the policy of research program and the public service at HE is based on the general policy of the HE Directorate, Ministry of National Education; 2) the implementation of policy in improving quality of HE still has constraints such as the institutions of research and public service are still separate, the socialization of programs of public service is still low, and most lecturers at HE are stil lack of having research methodolgy; 3) the research findings of both public and private HE can be implemented to develop and improve science. However, there has a few of the research findings that can be used for improving teaching and learning materials for higher education, very few of national as well international publications, and very few of having patent rights; and 4) the activities in public service are not based on the findings of the research yet.Â ABSTRAKTujuan penelitian adalah untuk mengetahui implementasi kebijakan dan pelaksanaan program penelitian dan pengabdian masyarakat pada perguruan tinggi (PT). Metode penelitian adalah metode campuran kuantitatif dan kualitatif dengan teknik analisis deskriptif. Sampel penelitian berjumlah 160 responden yang diambil secara purposive yaitu ketua/anggota lembaga penelitian dan pengabdian masyarakat di perguruan tinggi Negeri (PTN) dan perguruan tinggi Swasta (PTS). Penelitian dilaksanakan selama 7 bulan mulai bulan April sampai bulan Oktober 2008 di 6 provinsi yaitu provinsi Nusa Tenggara Barat (NTB), provinsi Bali, provinsi Daerah Khusus Yogyakarta (DIY), provinsi Jawa Barat, provinsi Sumatera Barat, dan provinsi Sumatera Utara. Alat dan teknik pengumpulan data adalah pedoman studi dokumentasi, kuesioner, wawancara, dan focus group discussion (FGD). Data primer adalah nara sumber di PT, sedangkan data sekunder adalah dokumen mengenai peraturan perundang-undangan dan penelitian penelitian terkait sebelumnya. Hasil penelitian adalah: 1) kebijakan program penelitian dan pengabdian masyarakat di PT berdasarkan kebijakan umum Direktorat Pendidikan Tinggi, Depdiknas; 2) implementasi kebijakan dalam meningkatkan kualitas pendidikan tinggi masih ada kendala antara lain lembaga penelitian dan pengabdian masyarakat masih terpisah, sosialisasi P2M masih kurang, dan kemampuan metodologi penelitian dosen masih rendah; 3) hasil-hasil penelitian yang dilaksanakan oleh PTN/PTS dapat dimanfaatkan untuk pengembangan dan peningkatan ilmu pengetahuan. Namun masih sedikit yang dapat dimanfaatkan untuk meningkatkan jumlah materi ajar, publikasi nasional/internasional, dan perolehan hak paten; dan 4) kegiatan pengabdian masyarakat belum berdasarkan hasil penelitian.